The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/jvi.78.14.7528-7535.2004
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Receptor 7 Expression by Effector/Memory CD4+T Cells Depends on Antigen Specificity and Tissue Localization during Influenza A Virus Infection

Abstract: The lung is an important entry site for respiratory pathogens such as influenza A virus. In order to combat such invading infectious agents, effector/memory T cells home to the lung and other peripheral tissues as well as lymphoid organs. In this process, chemokines and their receptors fulfill important roles in the guidance of T cells into such organs and specialized microenvironments within tissues. In this study, we determined if CD4 ؉ T cells residing in different lung compartments and draining lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 48 publications
2
53
1
Order By: Relevance
“…CCL19 and CCL21 expression has been identified in peripheral organs, such as the lung (27,43), but their role in host defense is not fully understood. Previous studies employing models of pulmonary infection have shown that CCR7 deficiency leads to impaired host defense (1,6,15,18,19,22,31). However, we demonstrated that CCR7 deficiency FIG.…”
Section: Discussioncontrasting
confidence: 52%
“…CCL19 and CCL21 expression has been identified in peripheral organs, such as the lung (27,43), but their role in host defense is not fully understood. Previous studies employing models of pulmonary infection have shown that CCR7 deficiency leads to impaired host defense (1,6,15,18,19,22,31). However, we demonstrated that CCR7 deficiency FIG.…”
Section: Discussioncontrasting
confidence: 52%
“…We have previously shown in a lung inflammation model that only effector T cells isolated from the tissue (or bronchoalveolar lavage fluid) have down-regulated CCR7 [43], suggesting a model of differentiation of both inflammatory as well as suppressor T cells from naive to antigenexperienced -but still recirculating -effector/memory cells to a final stage possessing the capacity to enter, but not to exit, the peripheral target tissue. We here provide evidence that forced accumulation due to CCR7 deficiency results in a significant increase in suppressive activity, confirming that Treg tissue exit via CCR7 contributes to the functional regulation of inflammatory responses.…”
Section: Discussionmentioning
confidence: 97%
“…In further support that antigen recognition by T cells in tissues leads to downregulation of CCR7 expression or function, previous studies show that while most infiltrating CD4 T cells are responsive to CCL21 (15), influenza virus-specific CD4 T cells in the infected lung are CCR7 Ϫ (15,47). In addition, Arnold and colleagues demonstrated that naïve CD4 T cells transiently reduce responsiveness to CCR7 ligands following antigen recognition in lymph nodes (2).…”
Section: Discussionmentioning
confidence: 99%
“…CD8 (clone 53-6.7), CD4 (clone RM4-5), and Thy1.1 (clone HIS51) rat anti-mouse monoclonal antibodies (eBioscience) were used to recognize surface markers. Binding of mouse CCL19 fused to human IgG (eBioscience) was used to stain for CCR7 as described previously (15). Human immunoglobulin G was used as a control.…”
Section: Methodsmentioning
confidence: 99%